2022
DOI: 10.1155/2022/6587221
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tai Chi Exercise for Patients with Type 2 Diabetes Mellitus: An Overview of Systematic Reviews and Meta-Analyses

Abstract: Objectives. Tai chi (TC) is a potential complementary treatment for type 2 diabetes mellitus (T2DM). This overview systematically summarizes and evaluates the existing evidence of TC in the treatment of T2DM. Methods. Systematic reviews (SRs)/meta-analyses (MAs) on TC interventions for T2DM were comprehensively searched in seven databases. Methodological quality, risk of bias, reporting quality, and quality of evidence were assessed using the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), the Risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Compared with the comparison group, the TCM exercises group performed better in the glycemic control and observed a significant decrease in FPG and HbA1c [69]. Several studies recommended Tai Chi as a prophylactic and therapeutic exercise prescription for type 2 diabetes [67,72,73,76,77], which not only improved FPG, 2hPG, HbA1c, triglyceride, high density lipoprotein cholesterol and life quality of people with type 2 diabetes compared with control groups (usual care, regular exercise and clinical conventional therapy) but also better played hypoglycemic effect than that of other aerobic exercises [72,73,76,77]. Moreover, the FPG level was lower in the Qigong group than in that of the resistance exercise group and the HbA1c level of the other aerobic exercise group, and the differences were statistically significant [71].…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the comparison group, the TCM exercises group performed better in the glycemic control and observed a significant decrease in FPG and HbA1c [69]. Several studies recommended Tai Chi as a prophylactic and therapeutic exercise prescription for type 2 diabetes [67,72,73,76,77], which not only improved FPG, 2hPG, HbA1c, triglyceride, high density lipoprotein cholesterol and life quality of people with type 2 diabetes compared with control groups (usual care, regular exercise and clinical conventional therapy) but also better played hypoglycemic effect than that of other aerobic exercises [72,73,76,77]. Moreover, the FPG level was lower in the Qigong group than in that of the resistance exercise group and the HbA1c level of the other aerobic exercise group, and the differences were statistically significant [71].…”
Section: Physical Activitymentioning
confidence: 99%
“…During the long history of TCM development, a variety of TCM therapeutic exercises have been formed [64], being proven to be suitable for central obesity management, thereby reducing the risk of related diseases [65], and have been recommended for the prevention and treatment of diabetes by Chinese guidelines [66]. Among them, Qigong, Tai Chi, Baduanjin and Yijinjing are most used in clinical experiments and show great potential in the prevention of type 2 diabetes [67][68][69][70][71][72][73][74][75].…”
Section: Physical Activitymentioning
confidence: 99%
“… 94 Tai chi is known as an effective way of managing blood glucose levels and HbA1c in patients with T2DM. 95 A recent meta-analysis showed that long-term practice of tai chi significantly lowers blood glucose levels and HbA1c in patients with T2DM. 96 Another meta-analysis including 798 individuals showed that tai chi is more efficient at lowering blood glucose levels (MD -1.39, 95% CI -1.95, -0.84; p<0.0001) and HbA1c (MD -0.21, 95% CI, -0.61, 0.19; p=0.31) compared with no exercise.…”
Section: Exercise Interventions For the Management Of Obesity And Typ...mentioning
confidence: 99%
“…Several researchers have shown that regular exercise inhibits and delays the development of type 2 diabetes [ 7 ]; however, most of the studies in the diabetes field were carried out analyzing the effect of aerobic (mainly running) or resistance exercise. In the review article “The Effects of Tai Chi Exercise for Patients with Type 2 Diabetes Mellitus: An Overview of Systematic Reviews and Meta-Analyses,” the impact of regular practice of tai chi, which is a series of calm physical exercises and stretches' movement in individuals with type 2 diabetes, was evaluated [ 8 ]. The authors concluded that Tai Chi is beneficial and safe for individuals with type 2 diabetes; however, due to few experimental research on the topic, professionals in the area should approach this conclusion with caution.…”
mentioning
confidence: 99%